Hubungan antara Dukungan Sosial Keluarga dan Adaptabilitas Karir pada Mahasiswa Tingkat Akhir - Olyn Silvania; Maria Laksmi Anantasari (Fakultas Psikologi Universitas Sanata Dharma, 2022)
The more difficult and varied changes, demands, and challenges in the world of work emphasize mature readiness to deal with them. Last year students need to prepare themselves with increase career adaptability. An external factor that may affect career adaptability is family social support. Family social support can facilitate last year students’ transition process from university to work and helps last year students to manage distress in deal with future work challenges. Thus, it is important to examine the relationship between family social support and career adaptability among last year student. We argue that there was positive relationship between family social support and career adaptability among last year student. This study employed quantitative research method with Spearman’s rho correlation technique as data analysis. The result showed a significant positive relationship between family social support and career adaptability among last year students (r= 0,375; p= 0,000). The research suggests that last year students should involve their family in career preparation in order to get information, advice, and suggestion which can become consideration to choose appropriate work occupation with interest and competence. Thus, it can ease the last year students’ adaptation process in work environment. Keywords: career adaptability, world of work, family social support, last year student